RECOGNITION TO WOMEN DURING THE REIGN OF SULTAN ALAUDDIN MANSUR SHAH 8TH RULER OF ACEH - KHAIRUL NIZAM BIN ZAINAL BADRI (Jurnal Al-Hikmah: Jurnal Dakwah, 2021)
While Europe is still struggling to get out of the Dark Ages; Aceh as the most influential government after the fall of Malacca, first adopted an open policy, whether in the fields of trade, education and governance. Furthermore, Aceh ahead of a policy of emancipation of women, that is to recognize the contribution and role of women based on their qualifications and ability. Sultan Alaudin Mansur Shah who was the 8th Sultan of Aceh perhaps is regarded as a pioneer in adopting this open policy; although studies of him are very rare in the archipelago. The study, based on sociology, in the context of this qualitative, conducted to determine the role and contribution of Sultan Alaudin Mansur Shah in promoting the development of women in Aceh. Also included in this study is the contribution and role of the students of Sultan Alaudin Mansur Shah named Malahayati, in the history of local government in Aceh. Significantly, the thought of Sultan Alaudin Mansur Shah in practicing this open policy; has led to foreign powers, especially Europe, respect and at the same time are terrified by the Aceh government.